2018
DOI: 10.5114/hm.2018.76076
|View full text |Cite
|
Sign up to set email alerts
|

Knee flexion and extension strength in young Brazilian soccer players: the effect of age and position

Abstract: Purpose. to compare isokinetic knee flexors and extensors concentric muscle strength in young soccer players of different ages and playing positions. Methods. Seventy-seven young male soccer players were divided into 3 age categories: U-15, U-17, and U-20, with the consideration of 4 game positions: goalkeepers, defenders, midfielders, and forwards. the concentric tests of the hamstrings (Hcon) and quadriceps (Qcon) were performed at 30°/s, 60°/s, and 180°/s, and the ratio of 180°/30° was calculated. Results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The specific work that goalkeepers often engage in separately from the rest of their teammates can make them stronger. The tendency of goalkeepers to have a higher PT can be observed in recent studies: Herdy et al 16 found that Brazilian goalkeepers also had the highest total values, although their sample was smaller than the one herein and their participants were younger than 20 years of age. Notably, in both the present study and that of Tsiokanos et al the goalkeepers were the heaviest players and had the highest PT values.…”
Section: Position On the Field Of Playmentioning
confidence: 53%
See 1 more Smart Citation
“…The specific work that goalkeepers often engage in separately from the rest of their teammates can make them stronger. The tendency of goalkeepers to have a higher PT can be observed in recent studies: Herdy et al 16 found that Brazilian goalkeepers also had the highest total values, although their sample was smaller than the one herein and their participants were younger than 20 years of age. Notably, in both the present study and that of Tsiokanos et al the goalkeepers were the heaviest players and had the highest PT values.…”
Section: Position On the Field Of Playmentioning
confidence: 53%
“…This trend at medium speeds has been found in several studies. 12,16,17 Therefore, one may question whether the position in the field truly determines the greater development of PT and the nature of the influence of variables such as weight, mass, height, and age, which may determine these higher values. However, the reality of soccer, as shown in this study, is that some players have a higher PT.…”
Section: Position On the Field Of Playmentioning
confidence: 99%
“…Another point that may influence the results is the lack of information on the young players' training routine. It is suggested that future studies describe this in more detail, as well as indicate the playing positions of the sample evaluated, as they can also impact on the results [38]. A need for prospective studies highlighting mechanisms that might increase injury risk in young players was also verified.…”
Section: Discussionmentioning
confidence: 98%